Involvement of pulmonary arteriopathy in the development and severity of reperfusion pulmonary edema after pulmonary endarterectomy. (May 2019) - Sanada, Takayuki Jujo; Tanabe, Nobuhiro; Ishibashi-Ueda, Hatsue; Ishida, Keiichi; Naito, Akira; Sakao, Seiichiro; Suda, Rika; Kasai, Hajime; Nishimura, Rintaro; Sugiura, Toshihiko; Shigeta, Ayako; Taniguchi, Yu; et al.
Reperfusion pulmonary edema (RPE) is a common complication after pulmonary endarterectomy (PEA) in patients with chronic thromboembolic pulmonary hypertension (CTEPH). However, the precise mechanisms underlying the development of RPE remain unclear. To evaluate the effects of pulmonary vasculopathy on RPE, the severity of the pulmonary arteriopathies and venopathies of lung tissues biopsied during PEA were pathologically quantified in 33 CTEPH patients. The severity of RPE was classified from grade 0 (no RPE) to 4 (death due to RPE) based on the arterial oxygen tension/inspiratory oxygen fraction (P/F ratio) and necessity of respiratory management. Among the 33 patients (27 women; mean age = 63.3 years), 17 (51.5%) patients developed RPE. The severity of pulmonary arteriopathy (obstruction ratio) correlated with the grade of RPE (r = 0.576, P  = 0.0005). The obstruction ratio also correlated with the P/F ratio (r = −0.543, P  = 0.001) and the perioperative mean pulmonary arterial pressure (r = 0.445, P  = 0.009). Multivariate logistic regression analysis revealed that the obstruction ratio was a significant independent determinant for the development of RPE (odds ratio = 15.7; 95% confidence interval = 2.29–108.00, P  = 0.005). In conclusion, pulmonary arteriopathy could be a determinant of the development and severity of RPE after PEA.